Media Literacy Education for Students During Learning Online the Covid-19 Pandemic - Fadhil Pahlevi Hidayat (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
One of the impacts of the COVID-19 pandemic is felt in the world of education, namely the Government's policy that all learning activities must be carried out from home online. With this policy, students tend to be affected by negative impacts during online learning due to the increasing consumption of the digital world. Therefore, media literacy education is needed for students so that it can become the basic ability of students to overcome negative and negative influences to improve understanding to build knowledge and have more critical thinking about information obtained from the media, especially for students who are currently learning from home online. This study uses a research method with a literature review with data collection techniques carried out through an in-depth study of various reference sources. The results of the analysis show that media literacy education for students during online learning during the covid-19 pandemic is a basic skill that is so important for a student to have, not only for online learning but also for learning in the 21st century as it is today. Media literacy education skills can be applied during online learning by applying skills such as access, select, understand, analyze, verify, evaluate, distribute, produce, participate and collaborate